Lead time reduction methods in a lean manufacturing environment: Master's thesis - Virrankoski, Atte (My University, 2025)
ABSTRACT: This research follows a manufacturing project of six products in a lean manufacturing environment. The lead times of these products are attempted to be shortened. The lead times in previous projects have been long, and the demand for this product is increasing. The literature review part of this thesis explores three different main theoretical frameworks for reducing lead time in a similar manufacturing environment: lean, the company's own model of continuous improvement, and process analysis and improvement subjects. Tools for reducing lead times are formed based on these subjects. Based on the previously mentioned frameworks, a plan of action is formed for reducing lead times. First, an "as-is" value stream map is formed, and a "to-be" state visioned. A five-step improvement plan is formed to achieve the "to-be" state. The first step is to improve the flow of information. Second, mapping the workflow with a swimlane diagram. Third, miscellaneous improvements that arise over the course of manufacturing. These three steps directly affect this manufacturing project. The next two are more long-term improvements for future projects. The first of these is data collection and research, and the other is semi-structured interviews. The results of the interview are analyzed both numerically and thematically. The "to-be" state is not achieved in all phases, but improvements on three out of four phases are, and the total lead time is achieved. Based on the results, a new "as-is" state and a "to-be" state are formed, and recommendations to achieve the new "to-be" state are given based on the research results and literature.

Tiivistelmä: Tässä tutkimuksessa seurataan kuuden tuotteen tuotantoprojektia lean-tuotantoympäristössä, joiden läpimenoaikaa yritetään parantaa. Tuotteiden läpimenoajat aiemmissa projekteissa ovat olleet pitkiä, ja niiden kysyntä on kasvussa. Kirjallisuuskatsauksessa käydään läpi kolme eri teoreettista viitekehystä läpimenoaikojen parantamiseen vastaavassa toimintaympäristössä: leania, yrityksen omaa jatkuvan parantamisen mallia, sekä prossessianalyysi ja -parannus otsikoiden alta. Näistä kehitetään erilaiset työkalut läpimenoajan tehostamiseen. Kirjallisuuskatsauksessa tutkittujen viitekehysten pohjalta kehitetään toimintasuunnitelma, jolla läpimenoaikoja lyhennetään. Ensin luodaan arvovirtakaavio tuotannon tämän hetkisestä tilasta, sekä tulevasta, tavoiteltavasta, tilasta. Tavoiteltavan tilan saavuttamiseksi kehitetään viisikohtainen parannussuunnitelma. Ensimmäisenä parannuskohtana toimii informaatiovirran tehostaminen. Toisena työjärjestyksen kartoittaminen uimaratakaaviolla. Kolmantena kohtana ovat sekalaiset parannuskohteet joita tuotannon aikana nousee esille. Nämä kolme kohtaa vaikuttavat suoraan tähän tuotantoprojektiin. Seuraavien kahden vaikutus kohdistuu enemmän tuleviin projekteihin. Ensimmäinen tällainen keino on datan kerääminen ja tutkiminen. Toisena puolirakenteisten haastatteluiden järjestäminen, joiden tuloksia analysoidaan sekä numeerisesti, että temaattisesti. Tavoiteltavaa tilaa ei saavuteta kaikilla vaiheilla, mutta parannuksia kolmella vaiheella neljästä, sekä kokonaisläpimenoajassa saavutetaan. Tuloksista muodostetaan uudet tämän hetkisen ja tavoiteltavan tilan arvovirtakaaviot, sekä kirjallisuuskatsaukseen että tutkimustuloksiin pohjautuva parannussuunnitelma joilla uusi tavoiteltava tila on saavutettavissa.
Keywords: processes; lean thinking; development (active); processes; production control; manufacturing; efficiency (properties); fi=Tuotantotalous (tekniikka)|en=Industrial Engineering and Management|; Master's Programme in Industrial Systems Analytics